Job Autonomy and Innovative Work Behavior in Nepalese Service Industry: Mediating Role of Creative Self-Efficacy - Basnet, Nabeena (Journal of Innovation in Academia, 2025)
This study investigates the mediating effect of creative self-efficacy in the relationship between job autonomy and innovative work behavior within the Nepalese service sector. A quantitative approach was used, and the data were collected purposively from 409 employees in the diverse Nepalese service sector. The data were analyzed using PLS-SEM in R software to examine the structural paths. Findings reveal that job autonomy positively influences innovative work behavior, with creative self-efficacy partially mediating the relationship. The results contribute to organizational behavior literature by highlighting psychological mechanisms underlying innovative work behavior in hierarchical contexts. Practical implications include fostering creative self-efficacy through training and structured autonomy to drive organizational innovation. Thus, the study emphasizes that strengthening both autonomy and creative self-efficacy is essential for enhancing employee innovation in service-sector organizations.